Mcmurray bedford inverter / Mohamed Rosman Mohamed Zawawi and Wan Roslan Wan Salleh - Mohamed Zawawi, Mohamed Rosman; Wan Salleh, Wan Roslan (1986)
Inverter is a circuit or device for converting d.c voltage to a a.c voltage, followed by step up transformer. In most cases, the output of the inverter is in a square form which contain a lot a of harmonic. To reduce these harmonic content, we use a pulse width , modulated technique and filter the output through the L.C filter.